Inclusive Differentiated Learning as A Strategic Foundation for Active Educational Participation - Muhammad Ikrom Karyodiputro (Yayasan Avicenna, 2024)
This study explores the implementation of inclusive differentiated learning as a strategy to increase student active participation. Using a qualitative case study approach, data were collected through semi-structured interviews, direct observation, and documentation. The results showed that adjusting materials, methods, and assessments according to students' needs and learning styles can increase engagement and create a more inclusive learning environment. Differentiated learning allows teachers to accommodate a variety of abilities, including students with special needs. The findings also emphasize the importance of ongoing training for teachers and the provision of adequate support facilities. Overall, inclusive differentiated learning has proven effective in addressing student ability gaps, creating more equitable learning, and improving the quality of education. This study recommends the development of policies that are more responsive to student needs and increased support for teachers.